Orbital fibroblasts of Graves' orbitopathy stimulated with proinflammatory cytokines promote B cell survival by secreting BAFF. (5th May 2017) - Tang, Fen; Chen, Xiaoqing; Mao, Yuxiang; Wan, Shangtao; Ai, Siming; Yang, Huasheng; Liu, Guangming; Zou, Yusha; Lin, Miaoli; Dan, Liang
Abstract: The success of rituximab for the treatment of active Graves' orbitopathy (GO) suggests that B cells play a critical role in intraorbital inflammation. B cell activating factor (BAFF) and its homolog a proliferation-inducing ligand (APRIL) are critical for B cell survival. However, the contribution of BAFF/APRIL to GO remains unclear. We sought to determine the role of BAFF/APRIL in the orbits of GO, and found that BAFF was markedly upregulated, while APRIL was not. Additionally, cultured GO orbital fibroblasts (GO-OFs) 2 expressing BAFF were induced to produce a large amount of BAFF. In contrast, a weak APRIL expression was detected in the OFs, and they exhibited a slight response to stimulation. Notably, pretreated GO-OFs promoted B cell survival, and this effect was significantly inhibited by a BAFF-R neutralizing antibody. This study indicates that OFs from GO can express BAFF and mediate the intraorbital survival of B cells via BAFF mechanism. Highlights: TNF-α, IFN-γ, and BAFF were upregulated in the retrobulbar tissues of GO patients. Cultured orbital fibroblasts produced BAFF following cytokine stimulation. Cultured GO-OFs overexpressed BAFF mRNA, and released much more soluble BAFF. Cultured OFs weakly expressed APRIL, and slightly responded to cytokines. GO-OFs promoted B cell survival by mechanisms involving BAFF.